2004
DOI: 10.1007/s00381-004-0954-y
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of inguinal complications after ventriculoperitoneal shunt for hydrocephalus

Abstract: The younger the age at which the VP shunt was performed, the higher the incidence of CIM. Bilateral manifestations were higher than in the normal population. Increased intra-abdominal pressure by accumulation of fluid in combination with the high patency rate of processus vaginalis possibly plays a role in the development of CIM in VP shunt patients. Bilateral repair should be considered even when CIM is unilateral. Special care should be given to repair procedures since the recurrence rate is relatively high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
0
25
0
4
Order By: Relevance
“…Clarnette et al [9] reported 15% of children developing inguinal hernia and 6% of boys developing hydrocele in 430 VP-shunt-inserted pediatric patients. Celik et al [1] also reported 21 cases (23.8%) with CIM after VP shunt insertion composed of 19 boys and only 2 girls. According to the reported cases in the literature, it is clear that CIM of VP shunt procedures are very rare in females.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Clarnette et al [9] reported 15% of children developing inguinal hernia and 6% of boys developing hydrocele in 430 VP-shunt-inserted pediatric patients. Celik et al [1] also reported 21 cases (23.8%) with CIM after VP shunt insertion composed of 19 boys and only 2 girls. According to the reported cases in the literature, it is clear that CIM of VP shunt procedures are very rare in females.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively raised pressure may convert a patent processus vaginalis from a potential to a clinical hernia. It is also reported that the incidence of patency of the processus vaginalis is higher in the first 6 months of life and intra-abdominal fluid accumulation in this period increases the risk of inguinoscrotal hernias and hydroceles [1, 9]. Our case was also admitted to our clinic when she was 5 months old.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations